Comparative effectiveness of pharmacologic and endoscopic interventions for prevention of post-ERCP pancreatitis: a network meta-analysis - Njei, Basile; McCarty, Thomas R.; Muniraj, Thiruvengadam; Sharma, Prabin; Jamidar, Priya A.; Aslanian, Harry R.; Varadarajulu, Shyam; Navaneethan, Udayakumar (Endoscopy International Open, 2020)
Background and study aims While several interventions may decrease risk of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis, it remains unclear whether one strategy is superior to others. The purpose of this study was to compare the effectiveness of pharmacologic and endoscopic interventions to prevent post-ERCP pancreatitis among high-risk patients.Methods A systematic review was performed to identify randomized controlled trials from PubMed, Embase, Web of Science, and Cochrane database through May 2017. Interventions included: rectal non-steroidal anti-inflammatory drugs (NSAIDs), aggressive hydration with lactated ringerʼs (LR) solution, and pancreatic stent placement compared to placebo. Only studies with patients at high-risk for post-ERCP pancreatitis were included. Bayesian network meta-analysis was performed and relative ranking of treatments was assessed using surface under the cumulative ranking (SUCRA) probabilities. Results We identified 29 trials, comprising 7,862 participants comparing four preventive strategies. On network meta-analysis, compared with placebo, rectal NSAIDs (B = – 0.69, 95 % CI [–1.18; – 0.21]), pancreatic stent (B = – 1.25, 95 % CI [–1.81 to –0.69]), LR (B = – 0.67, 95 % CI [–1.20 to –0.13]), and combination of LR plus rectal NSAIDs (B = – 1.58; 95 % CI [–3.0 to –0.17]), were all associated with a reduced risk of post-ERCP pancreatitis. Pancreatic stent placement had the highest SUCRA probability (0.81, 95 % CI [0.83 to 0.80]) of being ranked the best prophylactic treatment. Conclusions Based on this network meta-analysis, pancreatic stent placement appears to be the most effective preventive strategy for post-ERCP pancreatitis in high-risk patients.